Kegiatan Pencak Silat sebagai Sarana Pengembangan Nilai Religius Anak Usia Dini : Pencak Silat Activities as a Means of Development Religious Values of Early Childhood - Cahniyo Wijaya Kuswanto; Jatmiko, Agus; Riyani, Indah; Pratiwi, Dona Dinda (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This research discusses the relationship between pencak silat activities and religious values in early childhood as the initial stage of introduction. The formulation of the problem in this study is whether there is a relationship between pencak silat activities and the religious values of early childhood in South Lampung. The purpose of this study was to determine the relationship between pencak silat activities and the religious values of early childhood in South Lampung. This research uses quantitative correlation research methods with questionnaires and documentation as data collection tools. This study is a population study with a total of 25 children respondents who filled out the questionnaire instrument filled by the parents of the child who participated in pencak silat. The data collection technique used is a questionnaire. The validation test uses correlation data results which show a valid value> 0, 632. Reliability test with Alpa Cronbach (a) technique with SPSS version 29 tool that is> 0.70.  The results of the study say that the results of the product moment correlation calculation show that there is a positive relationship between pencak silat activities and the religious value of early childhood. Proven by the calculation of the product moment correlation rhittung> rtable with a value of 0.483> 0.396. These results conclude that this study shows a positive relationship between pencak silat and the religious values of early childhood that support physical development and religious values. The Role of Dopamine Stimulation Through Zakat Practices in Behavior Modification and Mental Health Improvement   ABSTRAK Penelitian ini membahas mengenai seberapa besar hubungan antara kegiatan pencak silat dengan nilai religius pada anak usia dini sebagai tahap awal pengenalan. Rumusan masalah dalam penelitian ini adalah apakah terdapat hubungan kegiatan pencak silat dengan nilai religius anak usia dini di Lampung Selatan. Tujuan dilakukannya penelitian ini untuk mengetahui hubungan antara kegiatan pencak silat dengan nilai religius anak usia dini di Lampung Selatan. Penelitian ini menggunakan metode penelitian jenis kuantitatif korelasi dengan angket dan dokumentasi sebagai alat pengumpul data. Penelitian ini merupakan penelitian populasi dengan jumlah responden 25 anak yang pengisian instrumen angket diisi oleh orang tua dari anak tersebut yang mengikuti pencak silat. Teknik pengumpulan data yang digunakan berupa angket. Uji validasi menggunakan correlation hasil data yang menunjukan nilai valid > 0, 632. Uji reliabilitas dengan teknik Alpa cronbach (a) dengan alat bantu SPSS versi 29 yaitu > 0,70.  Hasil dari penelitian mengatakan bahwa hasil perhitungan korelasi product moment menunjukan bahwa terdapat hubungan positif antara kegiatan pencak silat dengan nilai religius anak usia dini. Dibuktikan dengan perhitungan korelasi product moment rhittung > rtabel dengan nilai 0,483 > 0,396. Hasil tersebut menyimpulkan bahwa penelitian ini menunjukkan hubungan positif antara pencak silat dan nilai religius anak usia dini yang mendukung pengembangan fisik dan nilai religius.